Estimation of a Disequilibrium Aggregate Labor Market - Rosen, Harvey S.; Quandt, Richard E. (The Review of Economics and Statistics, 1978)
AN important question in contemporary 1AILeconomics is whether or not the real wage clears the labor market. Its answer has bearing on issues as diverse as the nature of unemployment, the efficacy of fiscal and monetary policies, and the incidence of income taxes. Unfortunately, consensus as to the correct answer seems to be lacking. While much of modern macroeconomic theory allows for the possibility that the real wage fails to equate the supply and demand of labor (Barro and Grossman, 1971; Korliras, 1975), much analysis is based on the assumption of equilibrium in the labor market (Patinkin, 1965). The purpose of the present paper is to carry out an econometric test for which view of the labor market is more appropriate. Although the model we build is very aggregative and much too crude to be used as a basis for policy, we believe that it provides a first step in making operational the theoretical literature on disequilibrium macro models. Our tentative conclusion is that the hypothesis of a labor market in continuous equilibrium must be rejected. In section II we describe briefly some earlier work on modelling the aggregate supply and demand for labor. It is shown that prior studies either assume equilibrium in the labor market, or deal with disequilibrium inadequately. In section III we specify the disequilibrium model. Section IV contains a discussion of estimation problems, an interpretation of the results, and a comparison with an equilibrium version of the model. A concluding section has a summary and an agenda for future research. II. Antecedents